Evaluation of tissue perfusion status in moderate to late preterm - Zhao, Y; Yang, G; Niu, S; Zhang, M; Gao, F; Liu, K (Physiological research, 2022)
The aim of this study was to investigate the tissue perfusion status and circadian rhythm in moderately premature infants. As a prospective study, from July 2019 to October 2019, the haemodynamic stability of moderate to late preterm, including such indicators as perfusion index (PI), blood pressure (systolic/diastolic) (BP), heart rate (HR), respiratory rate (RR), oxygen saturation (SpO2) and body temperature were monitored in the morning and at night within eight days after birth. There was no difference of statistical significance between PI values in the morning and at night (P>0.05). The HR from days six to eight after birth was higher than days one to three (P<0.05). The HR increased significantly on days seven and eight compared with days four and five (P<0.05). The BP from days three to eight was significantly higher than on day one (P<0.05), and the BP from days four to eight was higher than on day two. There was a weak positive correlation between the PI values and gestational age (GA) (r=0.097), HR (r=0.067) and time (r=0.284), and a negative correlation with SpO2 (r=-0.113). The PI and HR of moderate to late preterm increased within eight days after birth. BP was relatively lower after birth and gradually increased to a stable level on days three to four. The PI and BP circadian rhythms associated with tissue perfusion were not established on day eight after birth.
Keywords: srdeční frekvence; Infant, Newborn; Infant, Premature; novorozenec; Blood Pressure; Humans; prospektivní studie; Prospective Studies; perfuze; krevní tlak; Perfusion; Heart Rate; novorozenec nedonošený; lidé